Chladni and Fractal Dynamics: Dual Mode Marker to Map Cancer Cell Nucleus Disintegration Phases - Parama Dey; Anup Singhania; Ajaikumar B. Kunnumakkara; Subrata Ghosh; Anirban Bandyopadhyay (Fractal and Fractional)
Conventional cancer drugs are small molecules that target specific pathways. We introduced PCMS, a 26 kDa supramolecule combining sensors (S), molecular motors (M), and switching molecules (C), integrated within a fourth-generation PAMAM structure (P). PCMS identifies and deactivates cancer cell nucleus dynamics. A decade ago, we demonstrated programmable, clock-like interactions among the S-C-M components. In this study, we captured images of fractal patterns formed by chromosomal compartments and developed a theoretical model of their fractal dynamics. We showed that the nucleus behaves like a cavity, producing resonance effects similar to Chladni patterns. When the external agent, PCMS, interacts with this cavity, it generates a fractal pattern. We identified and mapped five key phase transitions that ultimately lead to the breakdown of cancer cell nuclei.